2011
DOI: 10.1038/jp.2011.180
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal antibiotic exposure in preterm infants with necrotizing enterocolitis

Abstract: Objective: To determine whether an association exists between antenatal antibiotic exposure and incidence of necrotizing enterocolitis (NEC) in low birth weight infants.Study Design: A retrospective case-control study was performed on all infants with a diagnosis of NEC born at our institition between 1988 and 2006. Medical histories of all infants with a diagnosis of NEC XBell's stage IIA and matched controls without NEC were reviewed. Maternal and neonatal characteristics were compared using the Mantel-Haens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 36 publications
0
33
2
1
Order By: Relevance
“…Premature neonates almost universally receive broad-spectrum antibiotics during their first two days of life and many receive more prolonged antibiotic courses for treatment of culture proven or “culture-negative sepsis”. Various retrospective studies have shown that prolonged antenatal 61 and post-natal antibiotic exposure is associated with an increased risk of developing NEC 6265 . Specifically, a retrospective analysis of 97 matched pairs showed that prenatal exposure to ampicillin was significantly greater in infants with NEC 61 .…”
Section: Necrotizing Enterocolitismentioning
confidence: 99%
See 1 more Smart Citation
“…Premature neonates almost universally receive broad-spectrum antibiotics during their first two days of life and many receive more prolonged antibiotic courses for treatment of culture proven or “culture-negative sepsis”. Various retrospective studies have shown that prolonged antenatal 61 and post-natal antibiotic exposure is associated with an increased risk of developing NEC 6265 . Specifically, a retrospective analysis of 97 matched pairs showed that prenatal exposure to ampicillin was significantly greater in infants with NEC 61 .…”
Section: Necrotizing Enterocolitismentioning
confidence: 99%
“…Various retrospective studies have shown that prolonged antenatal 61 and post-natal antibiotic exposure is associated with an increased risk of developing NEC 6265 . Specifically, a retrospective analysis of 97 matched pairs showed that prenatal exposure to ampicillin was significantly greater in infants with NEC 61 . Similarly, empirical (culture negative) antibiotics exposure for greater than 5 days has been associated with the development of NEC in numerous studies 6265 .…”
Section: Necrotizing Enterocolitismentioning
confidence: 99%
“…Evidence included in the eNEC™ and nursing intervention practice guide spanned evidence about NEC risk, 59–68 importance of feeding an exclusive human milk diet, 35 beginning trophic feeding early to avoid a prolonged NPO course, 69 careful but consistent advance of feeding, 70 a shared understanding about managing feeding intolerance, 13,71,72 and a consistent nursing response to communicate symptoms and initiate actions when NEC was developing. 43 …”
Section: Two Contemporary Nec Risk Toolsmentioning
confidence: 99%
“…Taken antenatally, these antibiotics may affect the neonatal gastrointestinal microbial flora. (6) Several studies also have shown that indomethacin, a nonselective cyclooxygenase inhibitor, given as a tocolytic agent to women in preterm labor, has been associated with neonatal NEC, perhaps by reducing mesenteric blood flow. (7, 8) In addition, there is a clear connection between fetal growth restriction and neonatal NEC, perhaps associated with chronic intrauterine hypoxia.…”
Section: Introductionmentioning
confidence: 99%